Modeling and Simulation of 4-DOF RRPR Manipulator Robot Using MATLAB - Permadi, Tesya; Ath Thahirah Al Azhima, Silmi; Al Qibtya, Mariya; Arief Hakim, Nurul Fahmi (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2024)
In recent decades, the rapid development of robotic technology has increased the demand for efficient and affordable robots, especially in the manufacturing industry. One type of robot that is commonly used is the robotic arm, which is capable of performing complex tasks with high precision and speed. This research focuses on the modeling and simulation of a 4-DOF RRPR robot manipulator using MATLAB software, including the SimScape Multibody Toolbox and Robotic System Toolbox. This study investigates various aspects of robot performance, such as joint angles, end-effector coordinates, and robot dynamics. With an emphasis on simulation, this research aims to accelerate the development of robotic technology and minimize the risks associated with physical implementation in the field. The simulation results provide valuable insights for improving the efficiency, precision, and reliability of robot manipulators in various applications. Furthermore, this research suggests future research directions, such as the exploration of advanced control systems to dynamically compensate for disturbances and the investigation of robots with higher degrees of freedom for more adaptive technology in challenging operational conditions.